Short-term effects of antimicrobial stewardship programs on antibiotics usage, clinical outcomes, and multidrug resistant organisms in the post COVID-19 era - Rania Tarek Helmi; Juhaina Salim Al-Maqbali; Sarah Gamal; Hashim Ba Wazir; Yousuf Al Sulemani; Mohammed Al Za'abi (Journal of Infection and Public Health, 2024)
Background: Antimicrobial resistance is associated with increasing mortality rates and the emergence of multidrug-resistant (MDR) organisms. There is scarcity of data on the short-term impact of Antimicrobial Stewardship Programs (ASP) on antibiotic usage, clinical outcome and MDR organisms’ pattern following the COVID-19 pandemic. This study evaluated the short-term effects of ASP on antibiotic usage, clinical outcomes and MDR organisms’ pattern in the post COVID-19 era. Methods: Conducted at a tertiary academic health center, this observational study involved adult patients (≥18 years) in the general medical unit, treated with oral or intravenous antibiotics from May 1, 2021, to April 30, 2022. The applied ASP strategy was a prospective audit and feedback where a weekly meeting was held to discuss the antimicrobial therapy of admitted patient, after which recommendations were made regarding antimicrobial use. Results: The study included 301 patients with 166 (55.1%) pre-ASP and 135 (44.9%) post-ASP. The median (IQR) age was 69 (55−77) years with 56.1% were female. Antibiotic usage dropped by 25.2% post-ASP. The length of hospital stay (LOS) was longer post-ASP (7 days vs. 7.9 days, p = 0.001), with MDR infections being a significant predictor (OR: 0.486, p < 0.001). There were no significant differences in 28-day readmission, recurrence of infections and all-cause mortality. Post-ASP, MDR pathogens increased (17.0% vs. 6.6%, p = 0.013), however, after separating post-ASP into two three-months periods, MDROs numbers decreased slightly (13 vs. 10). Conclusion: Short-term ASP implementation post COVID-19 reduced antibiotic usage while other clinical outcomes remained unchanged. Nonetheless an increase in MDR pathogens and LOS was observed. Further research is required to assess ASP’s long-term impact on MDR infections rates and specific patient group outcomes.